Analisis Pesan Dakwah di Channel Youtube Teladan Cinema pada Project Singlelillah - Nisa, Khairun; Arief, Suyyud; Ibdalsyah, Ibdalsyah (Universitas Ibn Khaldun Bogor, 2021)
In this day and age, da'wah is not only done in the mosque by ustadz from mimbar to mimbar. With the availability of highly advanced media in the 4.0 era, da'wah can be delivered in various ways, one of which is through social media. This research was conducted to find out whether the da'wah-da'wah carried out through social media really contains da'wah messages or not. In this thesis will discuss the da'wah messages in the video project